2021
DOI: 10.1111/jam.15115
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity, novel interactions and absence of well‐supported host‐guided phylogenetic groupings of Neotropical Alternaria isolates causing foliar lesions in Solanaceae

Abstract: Aim: To report the characterization of 120 Alternaria isolates inducing early blight-like foliar lesions in nine species of five Solanaceae genera collected across all macrogeographical Brazilian regions. Material and Results: Phylogenetic relationships were assessed via analyses of the Alternaria alternata allergenic protein-coding, glyceraldehyde-3-phosphate dehydrogenase and the calmodulin gene sequences. Most of the tomato isolates were placed into the Alternaria linariae cluster, whereas most of the potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Nevertheless, this nucleotide dataset allowed for the establishment of more precise phylogenetic relationships among the S. lactucae isolates. Low genetic diversity is consistent with predominantly asexual reproduction as also inferred for Alternaria species in Brazil (Lourenço Jr. et al 2009;Peixoto et al 2021). In the study of Lourenço Jr. et al (2009) were detected low number of mutations (n = 16), nucleotide diversity (0.007), and nucleotide differences (3.20) for Alt a1 gene.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, this nucleotide dataset allowed for the establishment of more precise phylogenetic relationships among the S. lactucae isolates. Low genetic diversity is consistent with predominantly asexual reproduction as also inferred for Alternaria species in Brazil (Lourenço Jr. et al 2009;Peixoto et al 2021). In the study of Lourenço Jr. et al (2009) were detected low number of mutations (n = 16), nucleotide diversity (0.007), and nucleotide differences (3.20) for Alt a1 gene.…”
Section: Discussionsupporting
confidence: 78%
“…Most of our collected isolates are small‐spored and belong to the Alternaria section Alternaria . The fact that only two isolates belong to section Porri is surprising because large spored species like A. linariae are reported as major problems on tomatoes (e.g., Peixoto et al, 2021). According to Adhikari et al (2020), A. alternata on tomato is neglected and poorly understood in comparison to A. linariae (Adhikari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only two isolates belong to section Porri is surprising, because large spored species like A. linariae are reported as major problems on tomato (e.g. Peixoto et al ., 2021). According to Adhikari et al 2020, A. alternata on tomato is neglected and poorly understood in comparison to A. linariae (Adhikari et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that hardly any A. solani was found on the wild tomatoes might indicate that there is no cross-contamination from crops to the wild. Peixoto et al 2021 found several Alternaria pathogens from different solanaceous plants in Brazil to cause early blight symptoms on tomato. As these had originally been collected from persistent weeds, they claim it is likely that these plants can act as alternative hosts and might become a source of inoculum to important crops (Peixoto et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation